I am preparing for an exam and I saw this exercise that our teacher left for us to prove:

Let $\{x_n \}_{n=1}^{\infty}$ be a sequence in a Hilbert space $\mathcal{H}$ such that $x_n \rightharpoonup 0$ or $\langle x_n, u \rangle \rightarrow 0$ for all $u \in \mathcal{H}.$

  1. Prove inductively that there exists a subsequence, $\{x_{n_k}\}_{k = 1}^{\infty}$ such that $\left| \langle x_{n_k}, x_{n_j} \rangle \right| \le \frac{1}{k}$ whenever $k > j.$
  2. For $N \in \mathbb{N}$, define $$y_N = \frac{1}{N}\sum_{k=1}^N x_{n_k}.$$ Prove that $y_N \rightarrow 0.$

For 1, I was thinking that there exists a convergent subsequence. For 2, I'm rather lost.


For $(1)$:

Since $\langle x_n, x_1\rangle \xrightarrow{n\to\infty} 0$, there exists a strictly increasing sequence $(p_1(n))_{n=1}^\infty \in \mathbb{N}$ such that $\left|\langle x_{p_1(n)}, x_1\rangle\right| < \frac1{n}, \forall n \in \mathbb{N}$.

Define $x_{n_1} = x_{p_1(1)}$.

Since $\langle x_{p_1(n)}, x_{p_1(1)}\rangle \xrightarrow{n\to\infty} 0$, there exists a strictly increasing sequence $(p_2(n))_{n=1}^\infty \in \mathbb{N}$ such that $\left|\langle x_{p_2(p_1(n))}, x_{p_1(1)}\rangle\right| < \frac1{n}, \forall n \in \mathbb{N}$.

Define $x_{n_2} = x_{p_1(p_2(2))}$.

Since $\langle x_{p_2(p_1(n))}, x_{p_2(p_1(2))}\rangle \xrightarrow{n\to\infty} 0$, there exists a strictly increasing sequence $(p_3(n))_{n=1}^\infty \in \mathbb{N}$ such that $\left|\langle x_{p_3(p_2(p_1(n)))}, x_{p_2(p_1(2))}\rangle\right| < \frac1{n}, \forall n \in \mathbb{N}$.

Define $x_{n_3} = x_{p_3(p_2(p_1(3)))}$.

Continue inductively, and define $x_{n_k} = x_{p_1(p_2(\ldots p_k(k)))} = x_{(p_1 \circ \cdots \circ p_k)(k)}$ for all $k \in \mathbb{N}$.

For $k > j$ we have by construction of $p_{j}$

$$\left|\langle x_{n_k}, x_{n_j}\rangle\right| = \left|\langle x_{(p_1 \circ \cdots p_{j} \circ p_{j+1} \circ \cdots \circ p_k)(k)}, x_{(p_1 \circ \cdots \circ p_j)(j)}\rangle\right| < \frac1{(p_{j+1}\circ p_{j+2} \circ \cdots \circ p_k)(k)} < \frac1{k}$$

because all $p_i$ are strictly increasing.


For 2:
$\Vert y_N \Vert^2 = \frac{1}{N^2} \langle \sum_{k = 1}^N y_{n_k}, \sum_{k = 1}^N y_{n_k} \rangle = \frac{1}{N^2} \sum_{k = 1}^N \sum_{j = 1}^N \langle y_{n_k}, y_{n_j} \rangle \leq \frac{2}{N^2} \sum_{k = 1}^N \sum_{j = k + 1}^N \vert \langle y_{n_k}, y_{n_j} \rangle \vert$.
At the last estimate we use that $\vert \langle y_{n_k}, y_{n_j} \rangle \vert = \vert \langle y_{n_j}, y_{n_k} \rangle \vert $.

Now we can use the properties of the sequence and further estimate
$\frac{2}{N^2} \sum_{k = 1}^N \sum_{j = k + 1}^N \vert \langle y_{n_k}, y_{n_j} \rangle \vert \leq \frac{2}{N^2} \sum_{k = 1}^N \sum_{j = k + 1}^N \frac{1}{k} = \frac{2}{N^2} \sum_{k = 1}^N \frac{N - k}{k} = \frac{2}{N}(\sum_{k = 1}^N \frac{1}{k} - 1) \to 0$.

  • $\begingroup$ Thanks, @eddie. This proof makes a lot of sense. I think you meant $x_{n_k}$ not $y+{n_k}$. $\endgroup$ – Harry Evans May 20 '18 at 23:45
  • $\begingroup$ @HarryEvans that's exactely what i meant ;) $\endgroup$ – eddie May 21 '18 at 7:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.